@David Mcmillan
–
O.k., thanks for the update. However, the fact that \(p(2) = 0\) won't imply that \(p(-\sqrt{2}) = 0\) either. On the other hand, if \(p(x)\) has integer coefficients then \(p(\sqrt{2}) = 0 \Leftrightarrow p(-\sqrt{2}) = 0\). This comes as a result of the irrational conjugate roots theorem, which states that for any polynomial \(p(x)\) with rational coefficients, if \(a + b\sqrt{c}\) is a root of \(p(x)\), where \(a,b\) are rational and \(\sqrt{c}\) is irrational, then \(a - b\sqrt{c}\) must also be a root of \(p(x)\).

To save some time, I'm just going to give you a link to a proof of the general theorem, (which was surprisingly hard to find). Scroll down to theorem 16 on page 14 for the desired proof. You can adapt this proof for the special case \(a = 0, b = 1\) to simplify it a bit. Good question; I don't think I've ever come across a proof of this theorem before. :)

Do you mean that if \(p(2) = 0\) then \(p(-2) = 0\)? If so, then this is not the case. If \(p(x) = x^{2} - x - 2\) then \(p(2) = 0\) but \(p(-2) = 4\). Perhaps you meant something else with the terminology "( -2 ) = 0"?

What can be said is that if a complex number \(z\) is a root of a polynomial then so is its conjugate \(\bar {z}\), i.e., \(p(z) = 0 \Leftrightarrow p(\bar {z}) = 0\).

This is the basic property of a polynomial equation. In fact, this is true for all rational coefficients. You try to prove it by taking a quadratic equation and then try to generalize that.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestdavid mcmillan see this

Same thing Sandeep Bhardwaj said

Log in to reply

But \(p(2) = 0\) doesn't imply that \(p(-2) = 0\). How else should I be reading "\(p(2)\) then \(( -2 ) = 0\)" ?

Log in to reply

Sir he meant - \(p(\sqrt{2})\)

Log in to reply

Sorry for the typo. I meant \( p(-\sqrt{2})\)

Log in to reply

To save some time, I'm just going to give you a link to a proof of the general theorem, (which was surprisingly hard to find). Scroll down to theorem 16 on page 14 for the desired proof. You can adapt this proof for the special case \(a = 0, b = 1\) to simplify it a bit. Good question; I don't think I've ever come across a proof of this theorem before. :)

Log in to reply

Do you mean that if \(p(2) = 0\) then \(p(-2) = 0\)? If so, then this is not the case. If \(p(x) = x^{2} - x - 2\) then \(p(2) = 0\) but \(p(-2) = 4\). Perhaps you meant something else with the terminology "( -2 ) = 0"?

What can be said is that if a complex number \(z\) is a root of a polynomial then so is its conjugate \(\bar {z}\), i.e., \(p(z) = 0 \Leftrightarrow p(\bar {z}) = 0\).

Log in to reply

@Calvin Lin @brian charlesworth @Sreejato Bhattacharya Please help.

Log in to reply

@Sudeep Salgia @Sandeep Bhardwaj Also try and help

Log in to reply

This is the basic property of a polynomial equation. In fact, this is true for all rational coefficients. You try to prove it by taking a quadratic equation and then try to generalize that.

Log in to reply